A study of Some English Phonological Rules and Their Processes - Idha Nurhamidah (Dinamika Bahasa dan Budaya, 2016)
This article discusses some English phonological rules and their phonological process. The rules dealt with in this article include aspiration, nasalization, vowel lengthening and regressive assimilation with fixed spelling—just to limit; despite the fact that there are more phonological rules. Each of the rules under study is described in terms of generative phonology followed data analysis to justify the application of the rules in line with the underlying forms. More significantly, the study will be able to give linguistic evidence that English has rules in their systems of sounds that are rule-governing and generative in nature   Key words: phonological rules and processes, aspiration, nasalization, vowel lengthening, regressive assimilation, rule-governed